Campodeidae (Hexapoda: Diplura) from Kyrgyzstan, Central Asia, with the description of a remarkable new genus and species - Sendra, Alberto; Sánchez-García, Alba; Selfa, Jesús; Milko, Dmitry A.; Ferreira, Rodrigo Lopes (European Journal of Taxonomy, 2021)
Samples collected in Central Asia, Kyrgyzstan, have revealed a hitherto unknown diversity of Campodeidae (Diplura) in soil and cave habitats, including a new genus and species, Kyrgyzstancampa sanare Sendra & Ferreira gen. et sp. nov., Turkmenocampa edaphica Sendra & Sánchez-García sp. nov. and a previously recognized soil-dwelling species, Campodea (Dicampa) catalana Denis, 1930. Kyrgyzstancampa sanare Sendra & Ferreira gen. et sp. nov. was collected in the deep zone of an interesting geological and cultural cave, Ak-Turpak Cave, located near the western margin of Kadamjay District, Batken Province. This genus belongs to the subfamily Campodeinae, sharing the morphology of the pretarsus with Eutrichocampa and other related genera, but differing from them in the shape of the claws and the laminar lateral processes, in addition to its unique cupuliform organ and the macrosetal pattern on the thorax and abdomen. Turkmenocampa edaphica Sendra & Sánchez-García sp. nov. was found in humid edaphic habitats, under stones or near roots, and is morphologically and geographically very similar to the cave-dwelling species Turkmenicampa mirabilis Sendra #38; Stoev, 2017, which occurs in an isolated cave in the nearby country of Turkmenistan.